Best Answer

x6 - y6 = (x3)2 - (y3)2 = (x3 + y3) (x3 - y3) = (x + y)(x2 - xy + y2)(x - y)(x2 + xy + y2)

Q: How do you factor x to the sixth minus y to the sixth?

Write your answer...

Submit

Still have questions?

Continue Learning about Basic Math

The factoring is as follows: x2 - y2 = (x + y) * (x - y)

x^2 - y^2 - 4 is in its simplest form.

3 * x * x * y

Assuming the missing sign is "minus" then you have the difference between two squares. This is solved as (x + y)(x - y). In your example x = 4a and y = 2b so the factorisation is (4a + 2b)(4a - 2b) or more completely: (4)(2a + b)(2a - b).

x^8 - y^8 = (x - y)(x + y)(x^2 + y^2)(x^4 + y^4)

Related questions

(x - y)(x + y)

it is (x-y)(x-y) :)

(x - y)(x + y)

The factoring is as follows: x2 - y2 = (x + y) * (x - y)

64 x cubed minus y cubed is (4x - y)(16x^2 + 4xy + y^2)

It is: (x-y)4

x^2 - y^2 - 4 is in its simplest form.

There are no rational factors.

To factor out the expression: x2y-y3 First factor out one "y": y(x2-y2) The expression x2-y2 is a difference of squares, which factors as well: (y)(x-y)(x+y) This is the simplest factoring of the original expression.

Let y= ab+(- a)(b) +(-a)(-b) factor out -a y= ab+(-a){b+(-b)} y=ab+(-a)(0) y =ab -------------------(1) now factor out b y= b{a+(-a)}+(-a)(-b) y= b(0) +(-a)(-b) y= (-a)(-b)-----------------(2) equate (1) and (2) (-a)(-b)=ab minus x minus = positive

y² - y - 6 = (y + 2)(y - 3)

X + Y (X + Y) ^2 = (X+Y)(X+Y) Factor = (X + Y)